Effectiveness of Slow Stroke Back Massage Therapy on the Sleep Quality of Postpartu Mother - Sihaloho, Endang; Dalimunthe, Selvian Yolanda; Simamora, Mery Krista; Ristiani, Ristiani (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The risk factors for non-typhoidal Salmonella infections in pediatric populations are not fully understood, but this remains a critical area of study for improving child health. Objective: The aim of this review is to systematically analyze the available literature about the risk factors of non typhoidal salmonella among pediatric populations. Method: The risk factors for non-typhoidal Salmonella infections in children were examined in all papers published between 2019 and 2024 using a systematic review of the literature using PRISMA criteria. Google Scholar, PubMed, and ProQuest are the three electronic databases that the writers searched. The query "children” AND “risk factors” AND “non-typhoidal salmonella” OR “salmonellosis" was used. The outcomes were then examined appropriately. Results: We initially identified 1983 articles and subsequently selected 7 articles that met the inclusion criteria. We identified several risk factors associated with non-typhoidal Salmonella infections and categorized them into four domains: environmental factors (such as open field waste disposal), behavioral habits (like inadequate handwashing), health conditions, and socio-demographic characteristics (such as lower parental education). Conclusions: Our review identified risk factors for non-typhoidal Salmonella infections in four domains: environmental factors, behavioral habits, health conditions, and socio-demographic characteristics.